English made easy - Hosler, Mary.; Branchaw, Bernadine ([S.l.] : McGraw-Hill Humanities/Social Sciences/Languages, 1993)
English Made Easy, 5/e by Hosler is a text-workbook for use in quarter or semester courses in business English or basic English skills. Fifty-one lessons presented in 12 units cover the essentials of grammar, punctuation, style, capitalization, number usage, word usage, and paragraph development. The user-friendly, four-page format for each lesson consists of two pages of instruction followed by two pages of exercises. New author Mary Margaret Hosler, is a well-known and highly respected postsecondary business educator. She replaces Bernadine Branchaw, who is deceased.